User-Centered Design Approaches to Enhance Employee Attendance Applications - Wahyu Maulana Prawiro; Egia Rosi Subhiyakto (Advance Sustainable Science Engineering and Technology, 2024)
In the current digital era, Human Resource Management (HRM) has undergone significant transformation with the advent of technology, including employee attendance applications. These applications replace inefficient and error-prone manual methods, facilitating effective attendance, leave, and monitoring of working hours. This study aims to apply a user-centered design (UCD) approach to developing an employee attendance application to enhance user experience (UX). Evaluation using the System Usability Scale (SUS) revealed a usability score of 86.37, classified as "Excellent." This score reflects positive user reception and underscores the importance of user-focused approaches in development. This research shows how user-tailored features can improve attendance management efficiency and effectiveness by aligning the application with user workflows. Despite the positive results of this study, recommended to continue periodic design iterations with regular user feedback to improve usability and satisfaction.